The plant endosphere world – bacterial life within plants. (4th October 2020) - Compant, Stéphane; Cambon, Marine C.; Vacher, Corinne; Mitter, Birgit; Samad, Abdul; Sessitsch, Angela
Summary: The plant endosphere is colonized by complex microbial communities and microorganisms, which colonize the plant interior at least part of their lifetime and are termed endophytes. Their functions range from mutualism to pathogenicity. All plant organs and tissues are generally colonized by bacterial endophytes and their diversity and composition depend on the plant, the plant organ and its physiological conditions, the plant growth stage as well as on the environment. Plant‐associated microorganisms, and in particular endophytes, have lately received high attention, because of the increasing awareness of the importance of host‐associated microbiota for the functioning and performance of their host. Some endophyte functions are known from mostly lab assays, genome prediction and few metagenome analyses; however, we have limited understanding on in planta activities, particularly considering the diversity of micro‐environments and the dynamics of conditions. In our review, we present recent findings on endosphere environments, their physiological conditions and endophyte colonization. Furthermore, we discuss microbial functions, the interaction between endophytes and plants as well as methodological limitations of endophyte research. We also provide an outlook on needs of future research to improve our understanding on the role of microbiota colonizing the endosphere on plant traits and ecosystem functioning.